Reliability Analysis for Rotary Feeder 561 BF 1 at PT Semen Bosowa Banyuwangi - Fauzi, Rifqi; Pramudyo, Cahyono Sigit (Proceeding International Conference on Science and Engineering, 2020)
Maintenance is an important activity in a manufacturing company. This paper focuses on reliability analysis for Rotary Feeder 561 BF 1 at PT Semen BosowaBanyuwangi. Mean Time to Failure and Reliablity were calculated. We concluded thatreliability at running time 240 hours or 10 days is 99.33%, while reliability damage at running hours 1920 hours or 80 days is 60.48% therefore before running hours 1920 equipment and materials need to be prepared for corrective maintenance.